Neck Trauma and Thyroglossal Cyst- A Delude Diagnosis - Chirakkal, Pramod; Hail, Amira Nasser Al; Burzeiza, Hala M Mohamed; Khafaji, Ali S. A.Al; Mashhadani, Shakir Mahmood Al (Archives of Clinical and Medical Case Reports, 2021)
The thyroid analogue arises from the floor of the primitive pharynx between the first and the second pharyngeal pouches. Originally hollow, it becomes solid as it migrates to the lower neck, the lower end dividing in to two portions that become the thyroid lobes. The stalk should atrophy at the sixth week but if it persists it becomes the thyroglossal duct in which cysts can develop. It runs from the thyroid gland behind, through or in front of the hyoid bone and ends deeply at the foramen caecum of the tongue. Very rarely, they may occupy the posterior hyoid space and present with dysphagia. We are presently sharing the clinical, pathophysiologic features and intraoperative findings of thyroglossal cyst mislead by neck trauma.